Root-To-Shoot Ratios of Flood-Tolerant Perennial Grasses Depend on Harvest and Fertilization Management: Implications for Quantification of Soil Carbon Input - Nielsen, Claudia Kalla; Jørgensen, Uffe; Lærke, Poul Erik (Frontiers in Environmental Science, 2021)
Quantifying soil organic carbon stocks (SOC) is a critical task in decision support related to climate and land management. Carbon inputs in soils are affected by development of belowground (BGB) and aboveground (AGB) biomass. However, uncertain fixed values of root:shoot ratios (R/S) are widely used for calculating SOC inputs in agroecosystems. In this study, we: (1) assessed the effect of harvest frequency (zero, one, two, and five times annually) on the root and shoot development of the perennial grasses Phalaris arundinacea (RCG), Festuca arundinacea (TF) and Festulolium (FL), (2) determined the effect of management on the carbon and nitrogen content in AGB and BGB, and (3) assessed the implications of R/S for SOC quantification. We found the highest yields of BGB in zero-cut treatments with 59% (FL) -70% (RCG) of total biomass. AGB yield was highest in the five-cut treatments with 54% (RCG) -60% (FL), resulting in a decreasing R/S with frequent management, ranging from 1.6 – 2.3 (zero-cut) to 0.6 –0.8 (five-cuts). No differences of R/S between species were observed. Total carbon yield ranged between 5.5 (FL, one-cut) – 18.9 t ha-1 yr-1 (FL, zero-cut), with a higher carbon content in AGB (45%) than BGB (40%). We showed that the input of total organic carbon into soil was highest in the zero-cut treatments, ranging between 6.6 – 7.6 t C ha-1 yr-1, though the two-cuts treatments showed the highest potential for carbon input (3.4 – 5.4 t C ha-1 yr-1) in the context of agricultural management. Our results highlighted that using default values for R/S resulted in inaccurate modeling estimations of the soil carbon input, as compared to a management-specific application of R/S. We conclude that an increasing number of annual cuts significantly lowered the R/S for all grasses. Given the critical role of BGB carbon input, our study highlights the need for comprehensive long-term experiments regarding the development of perennial grass root systems under AGB manipulation by harvest. In conclusion, we indicated the importance of using more accurate R/S for perennial grasses depending on management to avoid over- and underestimation of the carbon sink functioning of grassland ecosystems.